2016
DOI: 10.1158/1541-7786.mcr-16-0158
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Represses Metastasis inHer2-Postive Human Breast Cancer Cells by Suppressing RSK2 Expression

Abstract: The importance of the circadian/melatonin signal in suppressing the metastatic progression of breast and other cancers has been reported by numerous laboratories including our own. Currently, the mechanisms underlying the anti-metastatic actions of melatonin have not been well established. In the present study, the anti-metastatic actions of melatonin were evaluated and compared on the ERα-negative, Her2-positive SKBR-3 breast tumor cell line and ERα-positive MCF-7 cells overexpressing a constitutively active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…Regulation of ERK1/2 activity by melatonin has been reported to play important roles in the proliferation, migration, and differentiation of a variety of cell types, including neurons, immune, stem and cancer cells, and protective effects in diseases like multiple sclerosis (Álvarez‐Sánchez et al; Farez et al), cancer development (Mao et al), and atherosclerosis (Cheng et al). However, little is known about the respective role of the two melatonin receptors, MT 1 and MT 2 , and the signaling pathway(s) involved.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of ERK1/2 activity by melatonin has been reported to play important roles in the proliferation, migration, and differentiation of a variety of cell types, including neurons, immune, stem and cancer cells, and protective effects in diseases like multiple sclerosis (Álvarez‐Sánchez et al; Farez et al), cancer development (Mao et al), and atherosclerosis (Cheng et al). However, little is known about the respective role of the two melatonin receptors, MT 1 and MT 2 , and the signaling pathway(s) involved.…”
Section: Discussionmentioning
confidence: 99%
“…The principal EMT molecular features include loss of the epithelial marker E-cadherin, and overexpression of mesenchymal markers N-cadherin and vimentin [78,79]. Various studies also indicate that melatonin has anti-invasive and anti-metastatic effects, which involve multiple cellular processes including EMT [80][81][82].…”
Section: Effect Of Melatonin In Epithelial Mesenchymal Transition Marmentioning
confidence: 99%
“…Melatonin has also been shown to exert antiproliferative and cytotoxic effects on human cancers, including colorectal cancer [7], neuroblastoma [8], hepatocarcinoma [9], lung cancer [10-12], breast cancer [13], prostate cancer [14, 15], and leukaemia [16, 17]. In a gastric cancer cell line it was already shown that proapoptotic effect of melatonin could be due to activation of a Caspase-dependent pathway and inhibition of the nuclear translocation of NF-κB p65, two processes that are regulated by p38 and c-Jun N-terminal kinase (JNK) [18].…”
Section: Introductionmentioning
confidence: 99%